Caracterización del proceso de inclusión / exclusión en jóvenes universitarios de la carrera de Pedagogía Sede Cuenca de la Universidad Politécnica Salesiana - Roche Remache, Katherine Geovanna (2018)
The present work of titration called characterization of the process of inclusion/exclusion in young university students of the career of Pedagogy of the Polytechnic University Salesiana, seat of Cuenca, seeks to determine the types of inclusion and exclusion that are Have generated during the stay of young people in higher education. In such a way that the research addresses and responds to several questions: What are the main types of structural inclusion, which is evidenced within the career of pedagogy? What kind of exclusion, can be evidenced in the structural field, within the career of pedagogy? , for this reason, it was based on the experiential testimonies of students and teachers of the Universidad Politécnica Salesiana, who are in the process of qualitative research, through the technique of the interview. Finally, it is important to mention that the work of titration is structured in the following way, at first it is analyzed and contextualized the term social exclusion, by following explains the conceptual theoretical framework and finally presents The ethnographic findings, and analysis of results of the investigative work, where it is evidencio that the students of the aforementioned career were excluded by their cultural diversity, generational, gender identity, and by the socioeconomic level, however Types of inclusion were identified, such as the form of studies and attention to students with educational needs.